Sistem Penjaminan Mutu Internal dan Eksternal (BAN PAUD/PNF) - Yoshinta Putri Ariyanti; Fadilul Rahman (Inovasi Pendidikan dan Anak Usia Dini, 2025)
Early Childhood Education (PAUD) and Non-Formal Education (PNF) play a crucial role in human resource development, particularly during the early stages of individual growth. The Internal Quality Assurance System (SPMI) and the External Quality Assurance System (SPME) are key components in ensuring sustainable educational quality. SPMI focuses on self-evaluation by institutions to meet the National Education Standards, while SPME involves external parties for evaluation and accreditation. This study employs a literature review approach to assess the concepts and implementation of SPMI and SPME, as well as their impact on improving education quality in the PAUD/PNF sector. Findings indicate that the combination of these two systems can systematically, strategically, and sustainably enhance educational quality, although challenges such as inadequate facilities and irrelevant educator standards still need to be addressed. These quality assurance systems are vital in delivering high-quality education that supports children’s optimal development.